The Livestock and Meat Industry Council, Inc. (Kansas Agricultural Experiment Station Research Reports, 2018)
The Livestock and Meat Industry Council, Inc. (LMIC) is a non-profit charitable organization supporting animal agriculture research, teaching, and education. This is accomplished through the support of individuals and businesses that make LMIC a part of their charitable giving.